Vorticism : Cahier 8/9 - Mertens, Phil; Normand, T.; Davies, A.; O'Keeffe, P.; Fauchereau, S.; Cianci, G.; Gioe, V.; Beckett J. & Cherry, D.; Ind, R.; Robinson, K.; Cork, R.; Wilson, A. (Brussel : ICSAC, 1988)
Wyndham, Lewis ; Etchells, Frederick ; Langdon Coburn, Alvin ; Bomberg, David
boek